Dermatological manifestations of endocrine diseases (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Almost all endocrine diseases can be accompanied by damage to the skin and its appendages (hair and nails). Naturally, this is not always the leading symptom and often has a non-specific character. In other words, manifestations can occur in other conditions, not necessarily in diseases of the endocrine organ. Therefore, we, endocrinologists, do not rely on skin manifestations when making a diagnosis, since they are an additional plus in favor of any pathological condition.